Critical Thinking and Problem Solving Among Students - Heruna Tanty; Christopher Fernando; Jessica Valencia; Valentino Justin (Bina Nusantara University, 2022)
The development of the times is the background of increasingly rapid technological advances. The times have become the basis for the education industry to continue to grow. The development of education is expected to produce high-quality human resources and are able to think critically and creatively in solving problems. Quality education will lead to quality human resources as well. Critical thinking and problem solving as skills that need to be mastered by students, especially the younger generation. It has been widely recognized as one of the most important skills. Someone who has the ability to think critically and problem solving is considered to have many benefits because he has the ability to analyze certain situations and make the right decisions for the situation at hand. The research was conducted to determine the level of critical thinking and problem solving skills among students and students using three variables. The results of the study were analyzed using descriptive analysis to determine the distribution of data and inferential analysis to determine the level of validity and reliability. Validity is calculated to determine the level of data validity is above 95% or 99% and reliability is calculated to determine the level of data. The results of this study indicate that the level of a person's ability to identify problems affects the level of ability to solve the problems experienced. However, a person's ability to identify problems has no effect on the ability to make the right decisions on the problems experienced.